THE EFFECT OF COMMON ANXİETY DİSORDER ON JOB SATİSFACTİON (Third Sector Social Economic Review, 2023)
AbstractThe main purpose of this study; to determine the effect of generalized anxiety disorder on job satisfaction. The sample group of the research; it consists of white and blue-collar volunteers in various organisation within the province of Istanbul, regardless of the sector. In order to determine the population of the research, the number of registered employees in Istanbul was taken as a basis. It was determined that the most labor force was employed in the service and retail sectors and was chosen as the sample group. The sample group was reached by the convenience sampling method. Data were collected from 610 volunteers. Analyzes were applied to 582 valid questionnaires. The hypotheses were validated through correlation and regression analyses. According to the correlation analysis performed for the variables of the study; It was determined that there was a significant relationship between the two variables. This relationship was found to be negative and moderate. In other words, it has been determined that Generalized Anxiety Disorder reduces job satisfaction. In this interaction, it was determined that extrinsic satisfaction affects generalized anxiety disorder more. In addition, a difference was found in the analyzes performed for demographic variables.
Keywords: Organisational Behaviour; Organizational Behavior; Generalized Anxiety Disorder; Job satisfaction.